Synthesis and Antimicrobial Screening of the Metal Complexes with Cyanex 302 (Journal of Scientific Research, 2009)
The synthesis and characterization of metal complexes of the Cyanex 302 [bis(2, 4, 4-trimethylpentyl) monothiophosphinic acid] are reported. The complexes have been characterized by elemental analyses, molar conductivity, molecular mass determination and magnetic measurements, infrared and electronic spectral studies. The antibacterial and antifungal activities of the ligand and metal complexes have also been investigated. They have the stoichiometry of the type 1. [MgL2].H2O, 2. [Ca L2].H2O, 3. [ZrOL2].H2O, 4. [FeL3] and 5. [NiL2]. Electronic spectral data and the magnetic moment values suggested the complexes 1 and 2 are tetrahedral geometry, while the complexes 3, 4 and 5 are square pyramidal, octahedral and square planar geometry around the central metal ions, respectively. Besides, magnetic susceptibility measurements of the complexes also revealed that complexes 1-3 and 5 are diamagnetic in nature, except complex 4, which is paramagnetic. The metal complexes showed stronger antibacterial and antifungal activities than the ligand.  Keywords: Antibacterial, antifungal; Bis(2, 4, 4-trimethylpentyl) mothiophosphinic acid; Cyanex 302. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.2259              J. Sci. Res. 1 (3), 647-654 (2009)